2004
DOI: 10.1080/08958370490443204
|View full text |Cite
|
Sign up to set email alerts
|

Urban PM2.5Surface Chemistry and Interactions with Bronchoalveolar Lavage Fluid

Abstract: This study investigated the surface chemistry of urban fine particles (PM(2.5)), and quantified the adsorbed and desorbed species after exposure to bronchoalveolar lavage fluid (BALF). Urban background and roadside PM(2.5) samples of different mass concentration and total weight were collected in triplicate in the South Bronx region of New York City. Simultaneously, the concentrations of other atmospheric pollutants (CO, NO(x), SO(2), O(3), elemental carbon) were measured, and weather conditions were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…It is known that surfaces of bacteria are opsonised by lung proteins immediately on deposition. Recent evidence has shown that polymer adsorbants modify PM 2.5 surfaces, and this affects their behaviour in lung fluid (19,20,22). These processes may be important for marking of particles as targets for phagocytosis.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
See 2 more Smart Citations
“…It is known that surfaces of bacteria are opsonised by lung proteins immediately on deposition. Recent evidence has shown that polymer adsorbants modify PM 2.5 surfaces, and this affects their behaviour in lung fluid (19,20,22). These processes may be important for marking of particles as targets for phagocytosis.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
“…PM2.5 samples were gathered as reported by Kendall et al (19,21). Twelve triplicate samples of PM 2.5 were collected on PTFE filters in New York City (n ϭ 35; plus 1 lost sample).…”
Section: Pm2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the absence of characterisation of the nanoparticles in the two different media, it is not possible to make any interpretation of the data on the basis of whether the different protein coronas result in different available doses, which could potentially explain the different observed impacts [5]. In other studies, the surface chemistry profiles of airborne particle samples collected in different continents, and exposed to the lung lining liquid of different subjects, showed surprising consistency and resulted in similar aggregation effects [9].…”
Section: Effect Of Adsorption On Biomoleculesmentioning
confidence: 99%
“…The idea of airborne particulates becoming coated with lung surfactant lipid following inhalation was postulated in 1990 [6]. Proteins and lipids in lung lining liquid at the air-liquid (alveolar fluid, hypophase) interface -the first biostructure an inhaled nanoparticle encounters when deposited in the alveoli -were later observed to coat urban nanoparticles in a corona and cause nanoparticle aggregation [7][8][9].…”
Section: The Bio-nano Interface -Providing a Biological Identity To Nmentioning
confidence: 99%